Sirtulin–Ypk1 regulation axis governs the TOR signaling pathway and fungal pathogenicity in Cryptococcus neoformans - Zhenghua Chai; Yanjian Li; Jing Zhang; Chen Ding; Xiujuan Tong; Zhijie Zhang (Microbiology Spectrum, 2024)
ABSTRACT Cryptococcus neoformans is a life-threatening fungal pathogen that is a causative agent for pulmonary infection and meningoencephalitis in both immunocompetent and immunodeficient individuals. Recent studies have elucidated the important function of the target of rapamycin (TOR) signaling pathway in the modulation of C. neoformans virulence factor production and pathogenicity in animal infection models. Herein, we discovered that Ypk1, a critical component of the TOR signaling pathway, acts as a critical modulator in fungal pathogenicity through post-translational modifications (PTMs). Mass spectrometry analysis revealed that Ypk1 is subject to protein acetylation at lysines 315 and 502, and both sites are located within kinase functional domains. Inhibition of the C. neoformans TOR pathway by rapamycin activates the deacetylation process for Ypk1. The YPK1Q strain, a hyper-acetylation of Ypk1, exhibited increased sensitivity to rapamycin, decreased capsule formation ability, reduced starvation tolerance, and diminished fungal pathogenicity, indicating that deacetylation of Ypk1 is crucial for responding to stress. Deacetylase inhibition assays have shown that sirtuin family proteins are critical to the Ypk1 deacetylation mechanism. After screening deacetylase mutants, we found that Dac1 and Dac7 directly interact with Ypk1 to facilitate the deacetylation modification process via a protein–protein interaction. These findings provide new insights into the molecular basis for regulating the TORC–Ypk1 axis and demonstrate an important function of protein acetylation in modulating fungal pathogenicity.IMPORTANCECryptococcus neoformans is an important opportunistic fungal pathogen in humans. While there are currently few effective antifungal treatments, the absence of novel molecular targets in fungal pathogenicity hinders the development of new drugs. There is increasing evidence that protein post-translational modifications (PTMs) can modulate the pathogenicity of fungi. In this study, we discovered that the pathogenicity of C. neoformans was significantly impacted by the dynamic acetylation changes of Ypk1, the immediate downstream target of the TOR complex. We discovered that Ypk1 is acetylated at lysines 315 and 502, both of which are within kinase functional domains. Deacetylation of Ypk1 is necessary for formation of the capsule structure, the response to the TOR pathway inhibitor rapamycin, nutrient utilization, and host infection. We also demonstrate that the sirtuin protein family is involved in the Ypk1 deacetylation mechanism. We anticipate that the sirtuin–Ypk1 regulation axis could be used as a potential target for the development of antifungal medications.